A cavotricuspid isthmus pouch revealed to be a breakout site for gap conduction of recurrent common atrial flutter - Takayuki Sekihara (Clinical Case Reports, 2020)
Abstract A cavotricuspid isthmus pouch can be a breakout site for gap conduction of cavotricuspid isthmus block line. If the previous block line is electrically silent, high‐density 3‐D mapping and pouchgraphy are useful to find the pouch and ablate within it.